Evaluation of a multi-epitope vaccine PME for Pasteurella multocida in mouse model - Zhang, Rui; Dai, Lu; Jia, Yizhen; Qi, Haoran; He, Junfeng; Cheng, Jiaxin; Gao, Xuejun; Lei, Liancheng; Liu, Feng (Frontiers in Immunology, 2025)
Pasteurella multocida (P. multocida) is the pathogen responsible for swine pasteurellosis, which can impede their growth and even cause death, leading huge economic losses to the global pig industry. P. multocida can be divided into 5 serotypes, and existing vaccines have low cross-immunity protection. Therefore, developing a vaccine that can provide effective cross-protection is essential for preventing swine pasteurellosis and reducing the abuse of antibiotics. In this study, six dominant antigenic proteins of P. multocida (PlpE, OmpA, OmpH, VacJ, Omp87 and Cp39) were selected. Through bioinformatics methods, 20 B-cell epitopes, 7 CTL epitopes and 11 Th-cell epitopes were predicted. The multi-epitope antigen PME was constructed by connecting these epitopes with linkers, and then the recombinant protein His-PME and the recombinant plasmid pcDNA3.1-PME could effectively stimulate immunized mice to produce antibodies, IL-4 and IFN-γ. The protection rates of His-PME group and pcDNA3.1-PME group were 62.5% and 75% against P. multocida serotype A, and 87.5% and 100% against P. multocida serotype D, respectively. Furthermore, the pathological lung damages in the His-PME group and the pcDNA3.1-PME group were significantly alleviated, and the bacterial loads in lung tissues were significantly decreased. These results indicated that the subunit vaccine His-PME and the DNA vaccine pcDNA3.1-PME can effectively resist the infection of P. multocida and have good immunogenicity and cross-protection. Therefore, the multi-epitope vaccine PME can be regarded as a candidate vaccine for the prevention of P. multocida infection.